An instructional aid for courses in corrections: The correctional institutions environment scale - Waters, J. Eugene (American journal of criminal justice, 1979)
This paper describes the use of Moos’ (1974) Correctional Institutions Environment Scale (CIES) as a supplemental instructional technique in criminal justice courses on corrections. Utilization of the CIES (Form I) provides students with feedback on their values and goal orientations toward correctional programs, and provides a means to organize class discussions on correctional environments. Sample CIES profiles of students are presented, and various instructional uses are delineated.